Maternal and Neonatal Complications of Methamphetamine Use during Pregnancy. (19th April 2021) - Premchit, Suthanud; Orungrote, Nawabhorn; Prommas, Sinart; Smanchat, Buppa; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun
Abstract : Background . Methamphetamine abuse has been a significant problem in Thailand. The methamphetamine abuse problem also affects pregnant women. The study of pregnancy outcomes among methamphetamine users during pregnancy is currently limited. Objective . To determine maternal and neonatal complications among methamphetamine-abusing parturients. Materials and method . This historical cohort study was conducted at Bhumibol Adulyadej Hospital (BAH), Bangkok, Thailand, between January 2017 and December 2019. The total number of women was 206 who were equally divided into a study and control group. Pregnant women who tested positive for methamphetamine in urine tests during the intrapartum period were compared to the control group with no history of drug abuse. Results . Maternal outcomes: gestational hypertension was found to be significantly increased in the study group compared to the control group at 14.6 vs. 1.0% (OR 17.4, 95%CI 2.5-134.3). Preeclampsia with and without severe features were found at higher rates in the study group without statistical significance. There were no eclamptic cases in this study. Neonatal outcomes: preterm birth rate of pregnant women who have tested positive in their urine methamphetamine test was significantly higher than in the control group (33.3%, 11.7%, OR 3.7, 95%CI 1.8-7.7). Average birth weight in the study and control group was 2779.1 ± 486.7 and 3049.5 ± 510 gm, respectively ( p value < 0.001). Low APGAR score rates of both groups also had no significant difference. Conclusion . Methamphetamine use during pregnancy increased both maternal and neonatal complications in terms of gestational hypertension, preterm birth, and average birth weight.